2019
DOI: 10.3847/1538-4357/ab002a
|View full text |Cite
|
Sign up to set email alerts
|

Confirming Herschel Candidate Protoclusters from ALMA/VLA CO Observations

Abstract: ALMA 870 µm continuum imaging has uncovered a population of blends of multiple dusty starforming galaxies (DSFGs) in sources originally detected with the Herschel Space Observatory. However, their pairwise separations are much smaller that what is found by ALMA follow-up of other single-dish surveys or expected from theoretical simulations. Using ALMA and VLA, we have targeted three of these systems to confirm whether the multiple 870 µm continuum sources lie at the same redshift, successfully detecting 12 CO(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
82
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 135 publications
(207 reference statements)
2
82
0
Order By: Relevance
“…While some proto-clusters show most of their members with gas fractions in agreement with coeval field galaxies, as those presented in this work (see also , there is clear evidence that other structures have individual systems with large gas masses (e.g. Tadaki et al 2019;Gómez-Guijarro et al 2019), as discussed above. Discriminating between if these gas-rich systems exist preferentially in overdense environments or if they represent only outliers of the general population (note that this kind of outliers also exists in the field) requires deeper observations of complete samples, even deeper than the ones presented here.…”
Section: Gas Content and Gas Fractionsupporting
confidence: 83%
See 4 more Smart Citations
“…While some proto-clusters show most of their members with gas fractions in agreement with coeval field galaxies, as those presented in this work (see also , there is clear evidence that other structures have individual systems with large gas masses (e.g. Tadaki et al 2019;Gómez-Guijarro et al 2019), as discussed above. Discriminating between if these gas-rich systems exist preferentially in overdense environments or if they represent only outliers of the general population (note that this kind of outliers also exists in the field) requires deeper observations of complete samples, even deeper than the ones presented here.…”
Section: Gas Content and Gas Fractionsupporting
confidence: 83%
“…Most of the remaing sources, and all the galaxies with M ⋆ 10 10 M ⊙ , have gas fractions (or upper limits) in agreement with the field relation. Similarly, Gómez-Guijarro et al (2019) found some galaxies with large gas fractions (all of them with M ⋆ 6 × 10 10 M ⊙ ) despite showing SFEs consistent with the field. Nevertheless, most of these gas-rich galaxies lie above the main sequence, and therefore, might be more representative of the starburst population.…”
Section: Gas Content and Gas Fractionmentioning
confidence: 66%
See 3 more Smart Citations